Think talk write with pictured cards on human digestive system: impact of critical thinking skills - Yakobus Bustami; Yance Riyati; Hendrikus Julung (Universitas Negeri Jakarta, 2019)
The critical thinking skill is one of the high-level thinking skills needed by students in the teaching and learning process. This research aimed to determine the effect of Think Talk Write (TTW) based picture cards on students’ critical thinking skills of class VIII on human digestive system material in SMP Negeri 6 Ketungau Tengah. The research was a quantitative approach using the quasi-experimental design. The populations were all eighth-grade students of SMP Negeri 6 Ketungau Tengah consisting of 41 students. The samples were VIII A class total of 22 students for the experimental class and VIII B class total of 19 students for the control class. Instruments used essay questions to measure critical thinking skills. The data obtained were analyzed using descriptive and inferential analysis using the t-test. The descriptive analysis results in the TTW learning model showed that there was an increase in the mean value of students' critical thinking skills from pre-test to post-test by 66.34% and the conventional learning by 33.30%. The results of the inferential analysis show that there is a significant learning effect on students' critical thinking skills (p: 0,000 < 0.05). The mean value of the TTW learning model is better than the conventional learning. It is recommended that teachers be able to implement the TTW learning model based on picture cards in science learning to improve students' critical thinking skills.